Cervical intervertebral separation caused by trauma on post-mortem computed tomography: Possibility of a diagnosis based on intervertebral gas. (January 2022) - Kudo, Seina; Kawasumi, Yusuke; Usui, Akihito; Igari, Yui; Funayama, Masato; Ueda, Takuya; Ishibashi, Tadashi; Saito, Haruo
Abstract: Objectives: Gas is a common finding in cervical intervertebral separation. However, intervertebral gas is also found in many decedents without intervertebral separation. Here, we quantified intervertebral gas and examined its value in the diagnosis of cervical intervertebral separation. Methods: We retrospectively reviewed data from 1118 decedents who underwent post-mortem computed tomography (CT) and autopsy from May 2011 to July 2016 and selected those with cervical intervertebral gas with or without intervertebral separation. These data comprised 56 cervical intervertebral spaces with gas [intervertebral separation in 19 (33.9%)] in 43 subjects [intervertebral separation in 17 (39.5%)]. We categorised the decedents according to gas volume, position, and shape and determined the significance of the differences between the decedents with and without separation. Results: The gas volume did not differ significantly between decedents with and without separation ( p = 0.063). However, there were significant differences in the gas position between decedents with and without separation. In the sagittal plane: gas was seen in the "centred" position in the ventral-to-dorsal direction in more decedents without separation than in those with separation (p = 0.018). Gas was seen in the ventral-to-dorsal positions in more decedents with separation than in those without separation (p = 0.049). In the cranio-caudal direction, gas in the upper position was more common in decedents with separation than in those without separation in the sagittal plane (p = 0.03). In the coronal plane: gas was seen in the upper position more frequently in decedents with separation in the cranio-caudal direction than in those without separation (p = 0.001). A significant difference in gas shape was observed only in the coronal plane (p = 0.024); irregular gas was associated with decedents without separation. Conclusion: Gas in the ventral-to-dorsal and upper positions in the sagittal plane and in the upper position in the coronal plane was rather indicative of cervical intervertebral separation. An irregular gas shape in the coronal plane was indicative of degenerative changes. Highlights: Cervical intervertebral separations have gas as a common finding. Intervertebral gas findings are founded in many cases with and without intervertebral separation. Gas in some positions indicated cervical intervertebral separation. An irregular gas shape in the coronal plane indicated degenerative changes.